Perinatal outcomes in abruptio placenta - Tambawaala, Zenab; Kale, Deepali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abruptio placentae is an obstetric emergency where placenta completely or partially separates before delivery of the baby. It occurs approximately in one in 120 deliveries. It is an important cause of perinatal morbidity and mortality. Methods: This was a prospective hospital-based study design conducted over a period of 2 years, in the Department of Obstetrics and Gynecology at a tertiary care hospital in Mumbai comprising of 60 cases. Results: The incidence of abruption placentae in Present study is 0.51%. Authors had perinatal mortality in 6.6% of the cases. Out of 60 cases, 2 deaths occurred in utero. Out of the remaining 58 cases, 24 babies needed NICU care, out of them, 22 went home alive and 2 had neonatal deaths. Perinatal morbidity in the form of hyperbilirubinemia, CNS depression, septicemia, neonatal anemia and neonatal DIC were noted. Conclusions: High incidence of perinatal mortality in abruptio placentae is because of increased number of still births. In our studies, the perinatal mortality is 6.6% as compared to all other studies. This decline in perinatal mortality is due to improved obstetric care and excellent NICU facilities which are required for a majority of the cases.